Daun Sirsak (Annona Muricata L.) Efektif Menurunkan Kadar Gula Darah - Siti Fadlilah; Adi Sucipto; Nazwar Hamdani Rahil; Sumarni Sumarni (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Hyperglycemia can be managed by non-pharmacotherapy by consuming herbal plants. Examples of plants that can be used are soursop leaves. The study aims to determine the effect of soursop leaves on blood sugar levels in the people of Kuwaru Village, Poncosari, Sandakan, Bantul, Yogyakarta. This type of research is a quasi-experiment with pre and post-test control group. The sampling technique used consecutive sampling with a large sample of 86 respondents consisting of a control group of 43 respondents and an intervention group of 43 respondents. Research instruments are Glucometer and observation sheets. Data analyzed using the Mann-Whitney test. Median random blood sugar in the pretest and posttest control group was 94.00 mg/dL and 98.00 mg/dL. Median random blood sugar in the pretest and posttest intervention group 129.00 mg/dL and 105.00 mg/dL. The results of the bivariate control group (p = 0.202). The results of the bivariate intervention group (p = 0.005). The results of the bivariate control group and the intervention group (p = 0.019). There were differences in pretest and posttest blood sugar in the intervention group, it can be concluded that Soursop leaves effectively reduce the random blood sugar of Residents in Kuwaru Village, Poncosari, Srandakan, Bantul, Yogyakarta.